2011
DOI: 10.1177/0363546511412165
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Magnetic Resonance Imaging Results of Arthroscopic Full-Layer Repair of Bursal-Side Partial-Thickness Rotator Cuff Tears

Abstract: For bursal-side PTRCT, clinical outcomes and tendon healing showed good results at a minimum 2 years after surgery, with minimal damage to intact articular tendon fibers on postoperative MRIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Upon closer inspection of the studies involving bursal-side tears, a controversy remains regarding which surgical technique yields the best clinical outcome. Koh et al and Xiao and Cui achieved good clinical outcomes at 2-year follow-ups in their studies that included 38 and 48 patients, respectively, with high-grade bursal-side PTRCTs repaired arthroscopically by transtendon repair [11, 17]. Donohue et al reported similar good results with articular, intratendinous, and bursal high-grade partial tears repaired arthroscopically after conversion to full-thickness tears in a study including 20 patients in each group [18].…”
Section: Discussionmentioning
confidence: 99%
“…Upon closer inspection of the studies involving bursal-side tears, a controversy remains regarding which surgical technique yields the best clinical outcome. Koh et al and Xiao and Cui achieved good clinical outcomes at 2-year follow-ups in their studies that included 38 and 48 patients, respectively, with high-grade bursal-side PTRCTs repaired arthroscopically by transtendon repair [11, 17]. Donohue et al reported similar good results with articular, intratendinous, and bursal high-grade partial tears repaired arthroscopically after conversion to full-thickness tears in a study including 20 patients in each group [18].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors[ 13 14 ] have proposed to complete a full thickness tear and repair it, whereas others[ 15 16 17 ] believe that the normal articular sided tissue should be reserved because it can protect the repaired bursal side tendon and offer a good opportunity for healing of the repaired tendon. In addition, with preservation of an intact articular side tendon, some authors[ 16 17 ] tend to perform a full-layer repair whereas others[ 15 18 ] prefer to repair the outer layer only. In the present study, we preserved the healthy articular side tendon as much as possible and repaired the bursal flap back to the bone.…”
Section: Discussionmentioning
confidence: 99%
“…Koh et al . [ 16 ] reported good structural integrity (88% healing rate) on MRI after arthroscopic full-layer repair. Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…Also for bursal-sided PRCTs, several different techniques of in-situ repair have been described [35][36][37] , with similar results. Tear conversions to full-thickness rotator cuff tears and repair can also be performed with one of the various techniques for rotator cuff repair.…”
Section: Bursal-sided Partial Thickness Rotator Cuff Tearsmentioning
confidence: 97%